Implementasi Manajemen Bandwidth Menggunakan Router Mikrotik dengan Metode Hierarchical Token Bucket (Studi Kasus: SD Negeri 1 Sukasada) - Saputra, Putu Alta; Suarjaya, I Made Agus Dwi; Sasmita, Gusti Made Arya (JITTER : Jurnal Ilmiah Teknologi dan Komputer, 2022)
Internet network services become a major requirement in a process of exchanging data or information. Many jobs are helped by the use of internet services. Sukasada State Elementary School 1 is one of the schools located in the city of Singaraja. State Elementary School 1 Sukasada already uses internet services to support all kinds of activities and work. Problems arise when many people use the internet network. These problems can be overcome by performing bandwidth management using the Hierarchical Token Bucket method which is divided into several classes. The purpose of this study is to regulate the distribution of bandwidth so that internet services work optimally, and to compare before and after bandwidth management using the Hierarchical Token Bucket method. Testing is done by analyzing the quality of service based on TIPHON standardization. The results obtained after bandwidth management is done is that the Hierarchical Token Bucket method can work well so that the bandwidth for users is spread evenly, and based on the TIPHON standard, it gets an index value of 4 with a very good category.